معنى الإفساد وعلاقته بالتجويد عند المحدثيـن .......................................... Meaning of Ifsad and its Relation to Tajwid Among the scholars of Hadith - الغني, إيمان علي العبد (الدراسات الإسلامية, 2018)
This paper inquires into the technical connotations of the two terms employed by the scholars of Hadith namely, Ifsad and Tajwid and explains their relevance to the science of ilal (i.e. the causes for admitting or rejecting reports). According to the writer, the first term stands for recognizing a fault in a report that has been apporantly considered as “good” (jayyid) either due to some flaw in the narrator, in the text or due to some other stronger report. While the second term (tajwid) stands for a report that apporantly fufills the criteria of beening “good”. Therefore, the writer proceeds to show the relevance of these two terms to the science of ilal. The latter eventually determines the actual value of a report in terms of authenticity from different angles.